2020
DOI: 10.3390/molecules25143119
|View full text |Cite
|
Sign up to set email alerts
|

Self-Nanoemulsifying Drug Delivery Systems for Enhancing Solubility, Permeability, and Bioavailability of Sesamin

Abstract: Sesamin (SSM) is a water-insoluble compound that is easily eliminated by liver metabolism. To improve the solubility and bioavailability of SSM, this study developed and characterized a self-nanoemulsifying drug delivery system (SNEDDS) for the oral delivery of SSM and conducted pharmacokinetic assessments. Oil and surfactant materials suitable for SNEDDS preparation were selected on the basis of their saturation solubility at 37 ± 0.5 °C. The mixing ratios of excipients were determined on the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 36 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…When these nano-micelles enter the mucosal surface in the GI tract, they facilitate a relatively higher drug uptake vis-à-vis conventional drug solutions [3]. Phytochemicals previously formulated using SNEDDS for oral delivery include genkwanin [16], luteolin [17], silybin [18], diacerein [19], sesamin [20], 4-allypyrocatechol [21], bruceine D [22], epiisopiloturine [23], quercetin [24], isoliquiritigenin [25], tetrandrine [26], apigenin [27], myricetin [28], resveratrol [29], naringenin [30], silymarin [31], cannabidiol [32], liquiritin [33], glaucocalyxin [34], among others. Previously, we have shown that TQ encapsulation in the SLNs employing phospholipid as cosurfactant could improve its oral bioavailability [35].…”
Section: Introductionmentioning
confidence: 99%
“…When these nano-micelles enter the mucosal surface in the GI tract, they facilitate a relatively higher drug uptake vis-à-vis conventional drug solutions [3]. Phytochemicals previously formulated using SNEDDS for oral delivery include genkwanin [16], luteolin [17], silybin [18], diacerein [19], sesamin [20], 4-allypyrocatechol [21], bruceine D [22], epiisopiloturine [23], quercetin [24], isoliquiritigenin [25], tetrandrine [26], apigenin [27], myricetin [28], resveratrol [29], naringenin [30], silymarin [31], cannabidiol [32], liquiritin [33], glaucocalyxin [34], among others. Previously, we have shown that TQ encapsulation in the SLNs employing phospholipid as cosurfactant could improve its oral bioavailability [35].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the content and the solubility of sesamin in sesame oil, a certain amount of sesamin (30 and 60 mg) was added to 70 g sesame oil, and then the mixture was treated with ultrasound for 30 min, subsequently, the mixture was placed in a thermostatic magnetic water bath stirred for 4 h at 37°C ( 24 ). Sesamin and asarinin contents in all sesame oil samples were analyzed using HPLC-UV (high-performance liquid chromatography combined with ultraviolet detector) methods based on the pervious literature ( 25 , 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…Improving the absorption and distribution of lipophilic components like sesamin can be possible by dissolving oil or various nanocarriers, i.e., a self-nanoemulsifying drug delivery system (SNEDD). Wang summarized that after self-emulsification of SNEDDS, droplet size was dispersed by sesamin at 66.4 ± 31.4 nm with increased intestinal permeability, relative bioavailability, and absolute bioavailability by more than three-fold and 12.9-fold and 0.3% to 4.4%, respectively [ 57 ]. Iwamoto et al stated that mixing with turmeric oil could increase the bioavailability of sesamin [ 58 ], where sesame extract with a turmeric oil mixture of sesame extract and turmeric oil (MST) was fed to Slc:ddY mice, and found that serum sesamin contents in the MST-treated group were 23-fold higher compared to the control group (administering sesame extract alone).…”
Section: Sesamin With Nanoformulation To Increase the Bioavailabilitymentioning
confidence: 99%